Colour amplifies relief shading. Issue 1 (1st December 2019) - Kovesi, Peter
Summary: Relief shading has long been recognised as being an effective way of presenting data. However, the interaction of relief shading and colour is perhaps not widely understood, and many software packages do not combine shading and colour in a physically correct manner. When relief shading and colour are correctly exploited an enhancement of the perception of 3D is obtained and, at the same time, a dynamic range compression of the data can be achieved while still retaining a sense of the metric values of the data. However, on the other hand, an inappropriate use of colour has the potential to disrupt the 3D perception induced by relief shading. To obtain the maximum benefit from combining colour with relief shading a low contrast colour map should be used and the shading pattern should be applied to the colour image multiplicatively, not via a transparency blending as is often implemented in GIS packages.